Gustav Gloom and The Nightmare Vault - Castro, Adam-Troy (Castro, Adam-Troy. Gustav Gloom ;, 2013)
As Fernie and Gustav battle the Shadow Eater, who seeks The Nightmare Vault for his master, the evil Lord Obsidian, Fernie learns about Gustav's mysterious past and just what happened to his missing parents.